The Combination of Interferon-Alpha and Ponatinib Enables Faster and Deeper Molecular Responses in Patient with De Novo Blast Crisis of CML: Interferon-Alpha May Return as a CML Treatment - Kunio Hayashi; Kazuhiro Ikegame; Naoto Takahashi (Case Reports in Hematology)
In the era of tyrosine kinase inhibitor (TKI) treatment, its effectiveness in treating chronic myelogenous leukemia (CML) has been improved, ensuring the same prognosis as that of healthy people of the same age. However, there are some patients with de novo blast crisis that undergoes acute conversion from the time of diagnosis and does not respond to TKI treatment, especially in the older patients. Here, we present a case of an older patient with de novo lymphoid crisis who was first treated with a combination of TKI and chemotherapy, but it was difficult to maintain a durable deep molecular response (DMR). After he achieved major molecular response (MMR) or less, it was possible to suppress IS% to DMR by performing a combined treatment with interferon-α (IFN-α) and ponatinib. It is considered that DMR can be maintained by the combination of the two-way action of IFN-α, that is, the transfer of dormant CML stem cells to the cellcycle and the activation of a specific immune response to CML cells. This clinical result suggests the possibility of the re-emergence of IFN-α, which has been used a therapeutic drug in the past.